2020
DOI: 10.3892/ol.2020.11477
|View full text |Cite
|
Sign up to set email alerts
|

Gene silencing of indoleamine 2,3‑dioxygenase 1 inhibits lung cancer growth by suppressing T‑cell exhaustion

Abstract: Indoleamine 2,3-dioxygenase 1 (IDO1), which degrades the essential amino acid tryptophan, exerts immunosuppressive functions and serves a crucial role in multiple types tumor progression, including non-small-cell lung cancer (NSCLC) and melanoma. Recent studies have reported that T-cell exhaustion is increased during tumor progression, which impairs the antitumor immune response. However, the association between IDO1 and T-cell exhaustion during tumor progression remains unknown. The present study evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…IDO1 induces tumor-related immunosuppression by Trp depletion and Kyn accumulation, which result in dysfunction of natural killer (NK) cells/effector T cells and activate Tregs [ 4 ]. Previous data have manifested that IDO1 was highly expressed in multiple cancer tissues including ovarian cancer, and that a high expression level was associated with poor prognosis [ 5 , 6 , 7 , 8 , 9 ]. Okamoto et al found that 50% of ovarian cancer patients were IDO1-positive and that the overall survival was 11 months in patients with diffuse distribution compared with 41 months survival in patients with sporadic distribution [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…IDO1 induces tumor-related immunosuppression by Trp depletion and Kyn accumulation, which result in dysfunction of natural killer (NK) cells/effector T cells and activate Tregs [ 4 ]. Previous data have manifested that IDO1 was highly expressed in multiple cancer tissues including ovarian cancer, and that a high expression level was associated with poor prognosis [ 5 , 6 , 7 , 8 , 9 ]. Okamoto et al found that 50% of ovarian cancer patients were IDO1-positive and that the overall survival was 11 months in patients with diffuse distribution compared with 41 months survival in patients with sporadic distribution [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…47 Reduced IDO1 expression also inhibits T-cell exhaustion. 48 The up-regulation of IDO1 expression in hBM-MSCs could indicate that curcumin can enhance the immunomodulatory function of hBM-MSCs. The immunomodulatory action of curcumin-treated MSCs in autoimmune disease models and in heterologous transplantation should be examined in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…IDO1 can promote immune toleration through tryptophan catabolism and accumulation of tryptophan metabolites 47 . Reduced IDO1 expression also inhibits T‐cell exhaustion 48 . The up‐regulation of IDO1 expression in hBM‐MSCs could indicate that curcumin can enhance the immunomodulatory function of hBM‐MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In the tumoral context, the cardinal functions of IDO are tryptophan depletion and kynurenine upregulation, which tilt the balance to immunosuppression ( 98 ). Recently, Shang et al have demonstrated that the tumoral IDO knockdown can substantially decrease the PD-1 expression on T-cells and increase the IL-2 plasmatic level in lung cancer-bearing mice ( 99 ). In line with that, it has been estimated that 37% of melanoma specimens express IDO, which its expression is substantially associated with tumoral PD-L1 expression and nodal metastasis ( 100 ).…”
Section: How Do Melanocytes Transform Into Melanoma?mentioning
confidence: 99%
“…Since IDO can also be expressed from tumoral cells ( 99 , 100 ), the silencing of DC-derived IDO might not suffice to downregulate the produced IDO in the tumor microenvironment. Epacadostat is an oral inhibitor of the IDO1 enzyme.…”
Section: The Lessons We Have Learned and The Lessons We Should Learnmentioning
confidence: 99%